2004
DOI: 10.1107/s1744309104032166
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray characterization of a lectin fromCicer arietinum(chickpea)

Abstract: The lectin isolated from mature seeds of Cicer arietinum (CAL) agglutinates pronase-treated rabbit and human erythrocytes and its haemagglutination activity is inhibited by fetuin and desialated fetuin but not by simple monosaccharides or oligosaccharides. The puri®ed lectin is a dimer of molecular weight 43 000 Da composed of two identical subunits (MW 21 500), as con®rmed by SDS±PAGE. The lectin has been crystallized using the hangingdrop vapour-diffusion method at 295 K over a well solution containing 0.2 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…A few examples of plant lectins having basic pI are Artocarpus hirsuta lectin (8.5) [10], C. arietinum lectin (9.0) [3] and basic winged bean lectin (∼10.0) [19]. MoL is a glycoprotein containing 1.5% neutral sugar.…”
Section: Purification and Characterization Of Molmentioning
confidence: 99%
See 1 more Smart Citation
“…A few examples of plant lectins having basic pI are Artocarpus hirsuta lectin (8.5) [10], C. arietinum lectin (9.0) [3] and basic winged bean lectin (∼10.0) [19]. MoL is a glycoprotein containing 1.5% neutral sugar.…”
Section: Purification and Characterization Of Molmentioning
confidence: 99%
“…Most of the lectins are specific for simple sugars and their hemagglutination activity is inhibited by monosaccharides or oligosaccharides. In addition, plant lectins with complex specificity that are inhibited only by complex glycoproteins and not by simple sugars have also been reported; for example Cicer arietinum seed lectin [3] Scilla campanulata bulb lectin [4], Arisaema flavum tuber lectin [5].…”
Section: Introductionmentioning
confidence: 97%
“…Different chickpea genotypes might yield dissimilar lectin showing variation in carbohydrate specificities. Earlier report on chickpea stated that only fetuin and desialated fetuin inhibit hemagglutination activity (Katre et al, ). The reason behind this is tissue differentiation that takes place during seed development stages (Suseelan, Mitra, Pandey, Sainis, & Krishna, ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Cicer comprises of one cultivated ( Cicer arietinum L.) and 42 wild species (Singh, Sharma, Varshney, Sharma, & Singh, ). In a previous study, lectin from cultivated chickpea seeds was purified and crystallized (Katre et al, ). Recent report of Wang et al () refers to lectin isolated from cultivated chickpea showed growth inhibition of potato beetle larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Cicer arietinum L. lectin i;e CAL possessed complex-sugar specificity (Katre et al, 2005). The molecular weight of the native protein as determined by gel filtration using HPLC is 43 000 Da.…”
Section: Resultsmentioning
confidence: 99%